Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

Development of an enzyme-linked immunosorbent assay for Bartonella henselae infection detection. - Ferrara, F; Di Niro, R; D'Angelo, S; Busetti, M; Marzari, R; Not, T; Sblattero, D (Lett Appl Microbiol, 2014)
UNLABELLED: Several serological diagnostics rely on enzyme-linked immunosorbent assay (ELISA) to detect bacterial infections. However, for some pathogens, including Bartonella henselae, diagnosis still depends on manually intensive, time-consuming assays including micro-immunofluorescence, Western blotting or indirect immunofluorescence. For such pathogens, there is obviously still a need to identify antigens to establish a reliable, fast and high-throughput assay (Dupon et al. ). We evaluated two B. henselae proteins to develop a novel serological ELISA: a well-known antigen, the 17-kDa protein, and GroEL, identified during this study by a proteomic approach. When serum IgG were tested, the specificity and sensitivity were 76 and 65·7% for 17-kDa, respectively, and 82 and 42·9% for GroEL, respectively. IgM were found to be more sensitive and specific for both proteins: 17-kDa protein, specificity 86·2% and sensitivity 75%; GroEL, specificity 97·7% and sensitivity 45·3%. IgM antibodies were also measured in lymphoma patients and patients with Mycobacterium tuberculosis infection to assess the usefulness of our ELISA to distinguish them from B. henselae infected patients. The resulting specificities were 89·1 and 93·5% for 17-kDa protein and GroEL, respectively. Combining the results from the two tests, we obtained a sensitivity of 82·8% and a specificity of 83·9%. Our work described and validated a proteomic approach suitable to identify immunogenic proteins useful for developing a serological test of B. henselae infection. SIGNIFICANCE AND IMPACT OF THE STUDY: A reliable serological assay for the diagnosis of Cat Scratch Disease (CSD) - a pathological condition caused by Bartonella henselae infection - has not yet been developed. Such an assay would be extremely useful to discriminate between CSD and other pathologies with similar symptoms but different aetiologies, for example lymphoma or tuberculosis. We investigate the use of two B. henselae proteins - GroEL and 17-kDa - to develop a serological-based ELISA, showing promising results with the potential for further development as an effective tool for the differential diagnosing of B. henselae infection.
Keywords: Adolescent; Adult; Amino Acid Sequence; Antibodies, Bacterial; Antigens, Bacterial; Bacterial Proteins; Bartonella henselae; Case-Control Studies; Cat-Scratch Disease; Chaperonin 60; Child; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin M; Lymphoma; Male; Molecular Sequence Data; ROC Curve; Tuberculosis, Pulmonary; Young Adult

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.